Reviews and Responses for A Geospatial Approach to Modeling Airspace Risk Factors - Vincent-Boulay, Nicolas; Marsden, Catharine; Calvo Fernandez, Esther; Verdonk Gallego, Christian; Netjasov, Fedja (Journal of Open Aviation Science, 2025)
See detailed reviews and responses in the PDF file. DOI for the original paper: https://doi.org/10.59490/joas.2025.7402